Role-playing Method for Language Development in Elementary School - Muh. Zuhdy Hamzah; Nofvia De Vega; Rahayu; S. Sumihatul Ummah MS; Petrus Jacob Pattiasina (Journal of Childhood Development, 2023)
This study aims to explore and analyze the use of the role-playing method as a means of children's language development in primary schools. The study examined the impact of the role-playing method in improving speaking skills in children aged 6-8 years. In the study a qualitative research methodology. the research design was devised by selecting relevant participants, such as elementary school students and teachers involved in learning role-playing at State Elementary School 3 Pardasuka. The results showed that the role-playing method significantly contributed to children's language development in elementary schools. Active participation and social interaction in role-playing activities help improve children's speaking skills by being more confident and expressive. In addition, children develop better listening skills by acting as active listeners. The content analysis results showed improved vocabulary and understanding of language concepts through the role-play experience. It is hoped that the results of this study can contribute to developing more effective and enjoyable learning methods in supporting children's language development in primary schools